2008
DOI: 10.1128/iai.01667-07
|View full text |Cite
|
Sign up to set email alerts
|

The Toxoplasma gondii Dense Granule Protein GRA7 Is Phosphorylated upon Invasion and Forms an Unexpected Association with the Rhoptry Proteins ROP2 and ROP4

Abstract: The obligate intracellular parasite Toxoplasma gondii infects warm-blooded animals throughout the world and is an opportunistic pathogen of humans. As it invades a host cell, Toxoplasma forms a novel organelle, the parasitophorous vacuole, in which it resides during its intracellular development. The parasite modifies the parasitophorous vacuole and its host cell with numerous proteins delivered from rhoptries and dense granules, which are secretory organelles unique to the phylum Apicomplexa. For the majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 37 publications
(66 reference statements)
3
77
0
Order By: Relevance
“…S1). Two peptides of ROP4/7 were also identified in the ROP18-Ty immunoprecipitation (IP), which may reflect the previously described interaction between GRA7 and ROP4/7 (23). To validate the ROP18 binding partners identified by MS/MS, GRA7 was immunoprecipitated from WT RH strain vs. Δgra7 mutant parasites under similar conditions and analyzed by MS/MS.…”
Section: Significancementioning
confidence: 78%
See 1 more Smart Citation
“…S1). Two peptides of ROP4/7 were also identified in the ROP18-Ty immunoprecipitation (IP), which may reflect the previously described interaction between GRA7 and ROP4/7 (23). To validate the ROP18 binding partners identified by MS/MS, GRA7 was immunoprecipitated from WT RH strain vs. Δgra7 mutant parasites under similar conditions and analyzed by MS/MS.…”
Section: Significancementioning
confidence: 78%
“…Previous co-IPs also identified an interaction between the pseudokinases ROP4/7, ROP8/2, and GRA7 and demonstrated that these proteins become phosphorylated within the host cell (23). Deletion of either GRA7 or ROP8/2 alone did not decrease virulence, unlike the loss of ROP18, suggesting that GRA7 and ROP8/2 are not involved in regulating ROP18 function.…”
Section: Discussionmentioning
confidence: 95%
“…2C). A fraction of GRA7 is associated with the vacuolar network of tubular membranes rather than the PVM (Bonhomme et al ., 1998), and in addition, binding of GRA7 to ROP2 and ROP4 was shown (Dunn et al ., 2008), perhaps explaining the only partial decrease of vacuolar GRA7 amounts in the absence of ROP5.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, both phosphorylation and glycosylation have been reported for members of the ROP5/ROP18/GRA7 complex (Dunn et al ., 2008; Luo et al ., 2011; Treeck et al ., 2011). It is possible that some of these modifications may be involved in the interactions between components of the kinase complex.…”
Section: Discussionmentioning
confidence: 99%
“…All subsequent incubations were performed in phosphate-buffered saline (PBS) supplemented with 3% bovine serum albumin (BSA). The cells were permeabilized for 15 min with PBS supplemented with 0.2% Triton X-100 and subsequently were blocked in 3% BSA-PBS overnight at 4°C or at room temperature for 1 h. After incubation with the primary antibody, Alexa Fluor 594-and Alexa Fluor 488-conjugated secondary antibodies (Molecular Probes/Invitrogen) were used (25). Samples were viewed on an Olympus BX60 upright fluorescence microscope with a 100ϫ oil immersion lens, and images were acquired with Image-Pro Plus software or QCapture software (version 2.9.11.2).…”
Section: Methodsmentioning
confidence: 99%